Chapter Sprachkontaktdynamiken im aspektuellen System. Neue Evidenz zur Progressivperiphrase aus dem Zimbrischen von Lusérn - Bidese, Ermenegildo (Biblioteca di Studi Slavistici, 2023)
This article sets out to present a recent study of progressive and prospective periphrases in Cimbrian, a German-based variety spoken in Northern Italy. Our research complements a renewed interest in the grammaticalization processes of progressive periphrases in inland-German dialects and standard German, focusing on German-based dialects that are spoken in isolation, namely not under the roof of Standard German. In such varieties similar processes take place; they show, however, accelerated dynamics due to the contact situation and can, thus, shed light on the diachrony of German and its dialects. In relation to the aspectual constructions in Cimbrian, we discovered a previously undocumented perspective periphrasis, viz. soin drumauz + zu-INF, which, however, is destined to be discarded from the aspectual system of Cimbrian on account of the expansion of the more general periphrasis soin nå + zu-INF. In terms of the dynamics of contact-induced grammar change, our research confirms that new constructions in a contact language are not simply the replication of those in the donor language but, rather, represent the internal recombination of abstract features in the aspectual system of Cimbrian.